Interview of Robert Ivany, Army Aide to US President Ronald Reagan (1984-1986) - Pierre-Marie Loizeau (Revue LISA)
The interview of Dr. Robert Ivany, a high-ranking US Army officer with a 34-year career, covers his 1984-86 mission as Army Aide to President Ronald Reagan. His experience sheds light on the vast logistical organization surrounding the Chief of State. As he relates a number of interesting anecdotes, from Reagan’s relationships with Soviet leaders to commemorative ceremonies in Germany or troop reviewing in Japan, he also expresses his sincere admiration for the 40th president, praising his humanity and friendly character, and insisting repeatedly on his treatment of others with respect. However, this dithyrambic representation of Reagan is scattered with some of the usual clichés of the pro-Reagan rhetorical literature. Lacking in critical distance, Dr. Ivany loses sight of the man in full. His testimony nevertheless provides a rare and original look from within and should be read as a starting-point for further analysis.